Slaughter or sacrifice? : the religious rhetoric of blood sacrifice in the British and German armies, 1914-1919 - Gregory, A (2005)
In 1914 the language of sacrifice and redemption was everywhere. This thesis compares the responses of English Anglican and German Protestant military chaplains to the Great War (1914-1918). Instead of reconstructing their relationship with combatants, it reconstructs their mental worlds. Examining their diaries, sermons, letters, articles, and meditations,it traces their religious ideals of redemption through blood. It argues that chaplains on both sides of the front shared a moral language of redemptive sacrifice,articulating different permutations of the same idea. That moral language initially comprehended the war as an episode of salvation, correcting a crisis of modernity through sacred violence. War was interpreted as the culmination of the ‘social question,’the climax of the churches’ quest for community, social cohesion, the healing of class antagonism, the reclamation of the sacred. They proclaimed the war as a sacrament, a rite of purification that would purge modernity of its disorders, restore morality and renew piety. They commonly presumed a fallen, hedonistic and profane industrialised world, its social cohesion threatened by godless materialism, and its need for redemption. By blood the dead would purchase a cleansed, uplifted and redeemed society. Witnessing catastrophic bloodshed, the central moral problem for most chaplains was not high casualties alone. It was the threat that mass death would not morally and spiritually transform their societies. As the conflict escalated into attrition and stalemate, chaplains’ increasingly doubted whether war could be intrinsically redemptive, redefining the ideal as a duty of civilians to repay their blood-debt to the dead and justify the sacrifices of their compatriots. Because chaplains were implicated in mass death by virtue of their office,the ideal of redemption through war became more an obligation than perception, an ideal that must be pursued lest the sacrifices of soldier-martyrs be cheapened. Divergences and nuanced differences emerged that distinguished Anglican and Protestant perceptions of the moral and spiritual impact of the war. Intraconfessional divergences emerged, in England over the relationship with French Catholic iconography and patri-passionism, in Germany over the meaning of defeat and the legitimacy of the new political order it replaced the Wilhelmine constitution. However, the common moral language of redemptive sacrifice outweighs the confessional and national differences in their responses to mechanised slaughter.